The Influence of Leadership Style and Work Environment on Motivation and Its Impact on Employee Performance at the Community and Village Empowerment Service of East Tanjung Jabung Regency - Saputra, Rica; Zahari, M.; Akbar, Ali (Dinasti Publisher, 2025)
This study aims to determine the description of leadership style, work environment, motivation and employee performance at the Community and Village Empowerment Service of Tanjung Jabung Timur Regency and to determine and analyze the influence of leadership style and work environment on motivation and its impact on employee performance at the Community and Village Empowerment Service of Tanjung Jabung Timur Regency. This type of research uses descriptive verification research. This study uses the PLS analysis method. The results of the descriptive study explain that the total score of leadership style is 2144 in the good category. Then for the description of the work environment variable shows that the employee work environment at the Community and Village Empowerment Service of Tanjung Jabung Timur Regency is good with a score of 3191. Furthermore, the description of the motivation variable shows that the motivation score is 3721 in the high category. While the description of the employee performance variable shows that the score is 3709 in the high category. In addition, the results of this study also show that leadership style and work environment have a positive and significant influence on employee motivation and performance at the Community and Village Empowerment Service of Tanjung Jabung Timur Regency. Improving leadership style and the quality of the work environment will encourage increased employee motivation, which in turn has an impact on improving their performance. In addition, motivation has been proven to play an important role as a factor that strengthens the influence of leadership style and work environment on performance, so that both factors, both directly and through motivation, are able to provide a real contribution to improving employee performance.